Application of {[4,4′-BPyH][C(CN)3]2} as a Bifunctional Nanostructured Molten Salt Catalyst for the Preparation of 2-Amino-4H-chromene Derivatives under Solvent-Free and Benign Conditions - Zolfigol, Mohammad Ali; Yarie, Meysam; Baghery, Saeed (Synlett, 2016)
The bifunctional nanostructured molten salt [4,4′-bipyridine]-1,1′-diium tricyanomethanide has been employed as a highly efficient and powerful catalyst for the preparation of 2-amino-4H-chromenes. A wide variety of aromatic aldehydes was condensed with malononitrile and resorcinol, 1-naphthol or 2-naphthol under mild and solvent-free conditions. This protocol has the advantages of short reaction times, high to excellent yields, and straightforward workup.
Keywords: multicomponent reactions; molten salt; ionic liquids; solvent-free conditions